Archives of Psychiatric Nursing Vol.30, No 2,April 2016 - Redaksi (Elsevier, 2016)
- Differences Between Irish and Australian Psychiatric Nurses' Family-Focused Practice in Adult Mental Health Services - "It Didn't Kill Me. It Just Made Me Stronger and Wiser": Silver Linings for Children and Adolescents of Parents with Chronic Pain - Efficacy of Group Motivational Interviewing in the Degree of Drug Craving in the Addicts Under the Methadone Maintenance Treatment (MMT) in South East of Iran -...